AN ANALYTICAL STUDY OF SEXUAL HARASSMENT OF WORKING WOMEN IN INDIA - Chand Bibi; Rishi, Kamlesh (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Sexual harassment is one of the major problems faced by our women in all walks of life at present. We are making every effort to overcome this abnormally growing problem. One of those problems is sexual harassment which adversely affects the economic and social growth of women. All women have been considered subservient to men since the beginning and hence they are socially considered to be men's helpers. Sexual harassment can happen under various schemes. Though sexual harassment has been a living reality right from the personal life, recently it has been considered as a serious and real issue of sexual harassment, as this harassment is done by colleagues and administrator. Sexual harassment results in violation of the fundamental rights of women to equality under Article 14 and 15 of the Indian Constitution and the right to live with dignity and dignity under Article 21 of the Constitution and the right to practice any profession or to perform any job, movement or work which engages the right to a safe and secure environment from sexual harassment. We have made proper reforms in the legislature, executive and judiciary, yet why women feel so much about sexual harassment, why acts, laws are not made to protect and safeguard their lives. The methodology adopted for the research is both theoretical and non-theoretical methods, legislations, acts, etc. The field of this study will be conducted with the help of working women in various working fields in India. The focus of this study was the current main step on sexual harassment of working women and this step started to fill the gap in the literature that came. The aim of the study is to begin filling in the gaps in the operating literature and take a step forward to basically implement the sexual harassment of working women. Whether this atrocity against women remains an adaptable issue.